Empowering Local MSMEs through the Merah Putih Cooperative: A Conceptual Review - Arsya Putri Charnova; Hendra Riofita (INCARE, International Journal of Educational Resources, 2026)
This study aims to analyze the strategic role of the Merah Putih Cooperative in empowering local Micro, Small, and Medium Enterprises (MSMEs) through a systematic review of current literature. The method used is a Systematic Literature Review (SLR) by reviewing 10 relevant journals over the past ten years from the Google Scholar database. The results of the study indicate that the institutional strengthening strategy through the preparation of mandatory administration and revision of the Articles of Association (AD/ART) can increase member compliance by up to 90% and a sense of ownership by 40%. In terms of human resource development, the managerial training program increases manager competency by 35%, which has implications for operational cost efficiency by 20%. Digital transformation through the implementation of accounting systems and digital marketplaces has been proven to increase operational efficiency by up to 45% and expand online market access for MSMEs by up to 50%. In addition, active participation of local communities and support from national government policies in the target of establishing 70,000 village cooperatives are the main drivers in increasing members' income by an average of 25%. The conclusion of this study confirms that the synergy between strengthening governance, technology adoption, and government policy support creates a resilient and sustainable people's economic ecosystem for MSMEs at the rural level.